Differential cross-sections for the double photoionization of lithium - Kheifets, A.; Fursa, Dmitry; Bray, Igor; Colgan, J.; Pindzola, M. (2012)
We apply the convergent close-coupling (CCC) and time-dependent close- coupling (TDCC) methods to describe energy and angular resolved double photoionization (DPI) of lithium at arbitrary energy sharing. By doing so, we are able to evaluate the recoil ion momentum distribution of DPI of Li and make a comparison with recent measurements of Zhu et al. [Phys. Rev. Lett. 103, 103008 (2009)].